2015
DOI: 10.3389/fnana.2015.00098
|View full text |Cite
|
Sign up to set email alerts
|

Histological validation of high-resolution DTI in human post mortem tissue

Abstract: Diffusion tensor imaging (DTI) is amongst the simplest mathematical models available for diffusion magnetic resonance imaging, yet still by far the most used one. Despite the success of DTI as an imaging tool for white matter fibers, its anatomical underpinnings on a microstructural basis remain unclear. In this study, we used 65 myelin-stained sections of human premotor cortex to validate modeled fiber orientations and oft used microstructure-sensitive scalar measures of DTI on the level of individual voxels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 48 publications
6
127
0
2
Order By: Relevance
“…A model focused on the contribution of the constituent physiological characteristics of white matter would be ideal for future applications of the watershed model, e.g. to test the complementary roles of axonal structure vs. myelin fraction (Caspers et al, 2015, Seehaus et al, 2015). Because our model does not make specific predictions for specific cellular constituents (e.g., water fraction, axonal diameter, myelin density), we favour the use of a simple tensor measure of diffusion organisation, fractional anisotropy (FA).…”
Section: Methods and Experimental Proceduresmentioning
confidence: 99%
“…A model focused on the contribution of the constituent physiological characteristics of white matter would be ideal for future applications of the watershed model, e.g. to test the complementary roles of axonal structure vs. myelin fraction (Caspers et al, 2015, Seehaus et al, 2015). Because our model does not make specific predictions for specific cellular constituents (e.g., water fraction, axonal diameter, myelin density), we favour the use of a simple tensor measure of diffusion organisation, fractional anisotropy (FA).…”
Section: Methods and Experimental Proceduresmentioning
confidence: 99%
“…Nonetheless, DTI remains a powerful method for noninvasively estimating WM structure in the brain with high sensitivity, but low specificity. A number of DTI validation studies have examined the potential anatomical underpinnings of the diffusion signal in animal and human post-mortem tissue (Budde et al, 2007; Leergaard et al, 2010; Seehaus et al, 2015), however, these studies have relied on traditional 2D slide-based immunohistochemistry which have major limitations for examining complex 3D structures. Using 3D-immunohistochemistry (3D-IHC), we show that WM regions with highly coherent fiber orientations, such as subregions of the mouse stria medullaris and the corpus collosum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible to generate structural tensors from histological sections (Budde and Frank, 2012; Seehaus et al, 2015), and structure tensor informed fiber tractography (STIFT) has already been reported using high field gradient echo MRI (Kleinnijenhuis et al, 2012). A similar structural tensor approach could be applied to CLARITY-cleared tissue volumes (Ye et al, 2016), including blocks of human brain, for direct within-sample comparison to diffusion tractography.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that thresholds of normalized MD images with values around 0.3 can efficiently separate the images into CSF/non-CSF clustering maps [7]. Furthermore, thresholds of normalized FA images with values between 0.25 and 0.45 can separate images into WM/non-WM clustering maps [35]. By finding the maximum match (minimum difference) between clustering maps generated by using a range of thresholds around these values and different cluster maps of the selected SIs and unistable images generated by clustering algorithms, the unistable results point to similar threshold levels, but other SIs have a range of values (Figures 7 and 8).…”
Section: Resultsmentioning
confidence: 99%